Influence of medium parameters on somatic embryogenesis from hypocotyl explants of flax (Linum usitatissimum L.) : effect of carbon source, total inorganic nitrogen and balance between ionic forms and interaction between calcium and zeatin - Cunha, Ana (1999)
The effects of different carbon sources, total inorganic nitrogen concentration, nitrate to ammonium ratio and the interaction between calcium and zeatin (ZEA) levels on somatic embryogenesis from flax hypocotyl explants were studied in three independent factorial experiments. MS medium supplemented with the monosaccharides glucose or fructose at high concentrations (4%) gave consistently highly embryogenic cultures, with higher somatic embryos frequencies and higher growth rates when compared with media supplemented with sucrose or maltose. Although media with maltose had performed well in a 1 to 4% concentration range, media supplemented with sucrose at 4% appeared to inhibit the induction and development of somatic embryos. Independently of the effect of the nitrogen content, the balance between both ionic forms (NO3- and NH4+) played a dramatic role on the induction of somatic embryogenesis and somatic embryos growth. Nitrate is important to calli differentiation and growth and a high ammonium content increased somatic embryo frequency. The embryogenic vs. undifferentiated cell growth commitment of flax explants was determined by an interaction between calcium and ZEA levels, a high calcium/low ZEA affording very low embryogenic potencial and high calli biomass. A high ZEA concentration was essential for the normal development of somatic embryos.